2019
DOI: 10.1093/ehjci/jez024
|View full text |Cite
|
Sign up to set email alerts
|

Mid-term outcome of severe tricuspid regurgitation: are there any differences according to mechanism and severity?

Abstract: Aims Patients with significant tricuspid regurgitation (TR) addressed according the new classification in torrential TR may have different prognosis compared with just severe TR patients. We sought to determine distribution and mechanism of consecutive severe TR patients, in accordance with aetiology and severity by applying the new proposed classification scheme and their long-term outcomes. Methods and results Between Janua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(36 citation statements)
references
References 21 publications
0
35
1
Order By: Relevance
“…For Triluminate-the prospective single-arm multicenter trial for the TriClip System (NT size)-a TR reduction by ≥ 1 grade was obtained in 91% of patients [9]. In both the Triluminate trial and our analysis, a five-class grading scheme was used to assess the severity of TR [12], as massive or torrential TR, which are included in the five-class grading, are associated with a higher risk of death and readmission of HF [20]. Braun and Fam et al did not report TR reduction at discharge, but indicated a TR reduction to grade 2 + or lower in 85% of PASCAL cases and 69% for XTR patients.…”
Section: Discussionmentioning
confidence: 99%
“…For Triluminate-the prospective single-arm multicenter trial for the TriClip System (NT size)-a TR reduction by ≥ 1 grade was obtained in 91% of patients [9]. In both the Triluminate trial and our analysis, a five-class grading scheme was used to assess the severity of TR [12], as massive or torrential TR, which are included in the five-class grading, are associated with a higher risk of death and readmission of HF [20]. Braun and Fam et al did not report TR reduction at discharge, but indicated a TR reduction to grade 2 + or lower in 85% of PASCAL cases and 69% for XTR patients.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in advanced stages with massive or torrential FTR, marked remodeling of TV apparatus, and secondary RA and RV dysfunction due to longstanding volume overload, it may be more challenging to distinguish the primary cause of FTR 6,16 . However, the prognosis of massive/torrential FTR is severe 30,31 and there is likely little clinical benefi t in clarifying the pathophysiological sequence at this advanced stage of the disease. Figure 3 presents the main imaging features that may help in differentiating the atrial FTR from the ventricular FTR.…”
Section: Anatomy and Pathophysiologymentioning
confidence: 99%
“…Although this extended scale is not evidence-based, it may be useful to help better characterize the effect of transcatheter intervention on the TR grade. In addition, natural history studies show, that the prognosis of patients with "very severe" TR is significantly worse compared to patients with "severe" TR, thus suggesting, that any reduction of TR may result in improved outcomes and a reduction of mortality (36). However, long-term outcomes related to reduction in TR after transcatheter procedures are not currently available.…”
Section: Transthoracic (Tte) and Transesophageal Echocardiography (Tee)mentioning
confidence: 99%